Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Minat Konsumen Apartemen Gunawangsa Tidar Surabaya - Qori A’yuna; Aisyah Darti Megasari (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of Service Quality and Facilities on Consumer Interest at the Gunawangsa Tidar Apartment in Surabaya. This research uses Quantitative method. The data used are primary data and data collection techniques using questionnaires. The results of the analysis in this study indicate that the quality of service and facilities has a significant influence on the consumer intention, which can be seen from the results of multiple linear regression analysis with indicating a positive linear pattern, meaning that the quality of service and facilities increases the consumer interest in buying a unit.